TRANSFORMASI NOVEL AYAT-AYAT CINTA 2 KE DALAM FILM - Imam Akhmad; Ajeng Ayu Milanti (Institut Seni Budaya Indonesia Bandung, 2020)
ABSTRACTAre for the moment are ekranisasi or over its role in taking the spacecraft than one work to other the works of art of has largely initiated. One of a movies that is the result of the process the ekranisasi is a Ayat-Ayat Cinta 2 director Guntur soedhardjanto. The film is very well welcomed by, no less important than her first film managed to get the audience as many as 3 million. Because the movie Ayat-Ayat Cinta 2 is a film managed to attract community , writer interested analyze similar and different from the novel by the movie. To research is used intertexs analysis. The results of the analysis stated that of novels and found improvised film director Guntur soehardjanto transformation of figures in the form of a side and some narrowing of and transformation of the story line. It was done director because in short duration available in the movie. But, improvisation is not change in the main characters and storylines significantly.